Effects of aging and menopause on serum interleukin-6 levels and peripheral blood mononuclear cell cytokine production in healthy nonobese women - Kim, Oh Yoen (Springer Netherlands, 2011)
Inappropriate interleukin-6 production is thought to play a role in the development of several age-related conditions including atherosclerosis. This study aimed to determine whether aging affects circulating interleukin-6 (IL-6) levels. Healthy, nonobese women (n = 208, 44.5 ± 0.70 years, 22.4 ± 0.17 kg/m(2)) were categorized into four age groups (22–31, 32–41, 42–51, and 52–63 years; cross-sectional study). Cytokine levels in serum and those produced from peripheral blood mononuclear cell (PBMC) were measured. The oldest group had the highest circulating levels of IL-6 and oxidized low-density lipoprotein (ox-LDL) and higher PBMC production of IL-6, tumor necrosis factor-α (TNF-α), and interleukin-1 alpha (IL-1β). Additionally, significant interactions between age and menopause were found for serum IL-6 (P = 0.024), and TNF-α (P = 0.011) and IL-1β (P < 0.001) produced from PBMCs. Serum IL-6 levels positively correlated with age, waist–hip ratio (WHR), systolic blood pressure, circulating levels of TNF-α, IL-1β, and ox-LDL, and urinary 8-epi-prostaglandin F(2)α. Multiple stepwise regression models identified the following factors for contributing to serum IL-6 levels: serum IL-1β, menopause status, WHR, and serum TNF-α in mode I (R(2) = 0.302); serum IL-1β, age, serum TNF-α, and WHR (β = 0.197; P = 0.006) in model II (R(2) = 0.283). Sub-analysis was performed according to menopausal status. Serum IL-6 levels were positively associated with levels of IL-6, TNF-α, and IL-1β in PBMC supernatants (unstimulated) from postmenopausal women, whereas these were negatively associated in premenopausal women. In conclusion, circulating IL-6 levels may be interactively influenced by age and menopause. Additionally, estrogen deprivation after menopause may enhance PBMC cytokine production in postmenopausal women, resulting in increased IL-6 levels which are closely related to oxidative stress.